The impact of food insecurity on receipt of care, retention in care, and viral suppression among people living with HIV/AIDS in the United States: a causal mediation analysis - Bleasdale, Jacob; Liu, Yu; Leone, Lucia A.; Morse, Gene D.; Przybyla, Sarahmona M. (Frontiers in Public Health, 2023)
Introduction Attaining The Joint United Nations Programme on HIV/AIDS 95-95-95 targets to end the HIV epidemic by 2030 will require a greater understanding of the underlying mechanisms influencing care engagement among people living with HIV/AIDS (PLWHA). One such mechanism is food insecurity, defined as limited or uncertain access to food. Food insecurity has been shown to significantly impact HIV outcomes. Yet, few studies have examined the mechanisms through which food insecurity may influence these outcomes. We aimed to examine the effects of nutritional, behavioral, and mental health mechanisms through which food insecurity may impact HIV care continuum outcomes: receipt of care, retention in care, and viral suppression. Methods We conducted a cross-sectional study of 200 PLWHA in New York State, United States from May-August 2022. Participants were recruited using convenience sampling methods. Multivariable logistic regression models were conducted to examine the associations between food insecurity and care continuum outcomes (receipt of care, retention in care, viral suppression), adjusting for age, race, ethnicity, education, income, and marital status. Individual causal mediation analyses were conducted to assess whether behavioral, mental health, and nutritional mechanisms mediated the hypothesized associations. Results The median age of participants was 30 years (IQR: 27-37 years). The majority self-identified as Black (54.0%), male (55.5%) and straight/heterosexual (63.0%). Increasing severity of food insecurity was associated with greater odds of non-retention in care (aOR: 1.35, 95% CI: 1.07, 1.70) and viral non-suppression (aOR: 1.29, 95% CI: 1.08, 1.54). For the impact of food insecurity on non-retention in care, there was an indirect relationship (natural indirect effect; NIE) mediated through Body Mass Index (BMI) (ORNIE: 1.08, 95% CI: 1.00, 1.18). For viral non-suppression, there was an indirect relationship mediated through BMI (ORNIE: 1.07, 95% CI: 1.00,1.16) and an indirect relationship mediated through depression (ORNIE: 1.27, 95% CI: 1.07, 1.47). Discussion Food insecurity was associated with greater odds of non-retention in care and viral non-suppression among PLWHA. Nutritional and mental health pathways are important mediators of these relationships. Results highlight the need for interventions to target these pathways to address food insecurity as an underlying mechanism influencing engagement in HIV care.